The Effect of Different Level Concentrate Supplementation on The Base Feed By Using Carrot Leaf Waste in Characteristics of Local Rabbit Carcass (Lepus nigricollis) - D. B. K. G. R., Paramartha; Nuriyasa, I M.; Puspani, E. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This study has been conducted for 3 months (12 weeks).  The aims of this study is to determine the effect of different level concentrate supplementation on the base feed by using carrot leaf waste in  characteristics of local rabbit carcass. The rabbits used in this study were local rabbits consisting of 20 rabbits aged 5 weeks. The basic feed used was carrot leaf. This study was using Randomized Block Design(RBD) with four treatments, each treatments ware repeated five times and each unit using one local rabbit. This study used four treatments: concentrate supplementation (R) consisting of not supplementation as control ration (R0), 15g concentrate supplementation (R1), supplementation 30g (R2) and 45g concentrate supplementation (R3). The variables observed were cutting weight, carcass weight, carcass percentage and carcass commercial cutting percentage. The result of this study showed that R3 treatment made the cutting weight and carcass weight was higher (P>0.05) than R0, R1 and R2. The Carcass percentage and carcasses commercial cutting weight including Foreleg, Hind leg, Loin and Rack showed a non significant between R3 treatment and rabbits with different concentrate supplementation (P<0.05). Based on the result of this study, the conclusion can be drawn that the characteristics of local rabbit carcasses given basic feed based on carrot leaf waste supplemented with 45g/day concentrate resulted the higher carcass weight than rabbits given concentrate supplementations 30g/day, 15g/day, and not supplementationconcentrate. Keywords: rabbit, carrot leaf, concentrate, carcass characteristics